Transhumanistic cybercrime analysis using a posthuman criminology approach to digital identity threats in artificial intelligence era - Jumantoro, Tegar Raffi Putra; Firdausy, Muhammad Kuttub (Privietlab, 2025)
The emergence of artificial intelligence has disrupted conventional legal assumptions about identity, subjectivity, and criminal responsibility. This study investigated the normative and systemic inadequacies of Indonesia’s legal system in responding to transhumanistic cybercrime, particularly involving the manipulation of digital identities. Employing a normative juridical method and incorporating statutory, conceptual, and comparative approaches, this study critically analyzes structural, substantive, and cultural inertia within the legal framework. Drawing on Lawrence Friedman’s legal system theory and post-human criminology, this study identifies a deep ontological crisis wherein non-human actors and synthetic identities remain legally unrecognized. A comparative analysis of the European Union, the United States, Estonia, and Japan illustrates the varying degrees of legal adaptation, from algorithmic accountability to digital identity sovereignty. The findings reveal that Indonesia lacks a coherent legal regime to address algorithm-driven harm or recognize digital identity as an autonomous legal subject. The study proposes legal reforms that include establishing a dedicated legal framework for digital identity protection, extending criminal liability to autonomous systems, and integrating post-human perspectives into legal education. In the age of algorithmic governance, law must transcend biological essentialism to remain legitimate, responsive, and just.